PENGARUH DOSIS DAN FREKUENSI PEMBERIAN PUPUK UREA TERHADAP PERTUMBUHAN DAN HASIL PETSAI DI BAWAH TEGAKAN SENGON UMUR 1,5 TAHUN - ROCHMADI ROCHMADI; HARJANTO HARJANTO; HARYUNI HARYUNI (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2006)
This Research porpose to know the effect of dose and gift frekuensi fertilize the urea and also interaction of both to growth and result of crop petsai (Brassica Pekinensis L) at strightened of sengon ( Paraserianthes Fakataria). Research have been executed at date of 28 March 2006 to 30 May 2006, in Countryside Tumenggungan, Subdistrict of Selomerto of Regency Wonosobo, Province of Central Java with the place height 850 m is above sea level. Research use the factorial method of elementary pattern of RAKL (Random Device of Complete Group) with two treatment factor that is 1) Dose fertilize the urea ( D) consisted of by 3 level : D1 50 kg / ha, D2 = 75 kg / ha, D3 = 100 kg / ha 2) Gift frekuensi fertilize the urea (F) consisted of by 3 level : F1 momentary before planting, F2 = frekuensi plant and after crop old age the two week, F3 = momentary before planting, after crop old age two and four weeks. Result of research show the 1) Dose treatment fertilize the urea have cm effect on very real at high of crop, sum up the leaf plant, fresh heavy of dry brangkasan plant weight and consume the plant 2) treatment of gift frekuensi fertilize to have an effect on very real to fresh weight of crop ready to consumption, heavy run dry the crop ready to consume, but do not have an effect on the reality differ is not real at high of crop, sum up the leaf plant. fresh heavy of brangkasan plant, and dry weight of brangkcisan plant 3) Interaction usher the treatment of dose and its gift frekuensi have an effect on the reality of at high of thy weight and crop of brangkasan plant of but having an effect on is not real to amount of leaf plant, fresh heavy of .fresh brangkasan plant weight and consume the plant 4) fresh Heavy of highest consumption 297,90 g /plant, obtained at combination of D3 F3 ( dose urea 100 kg / ha given momentary before planting, after crop old age two and four weeks). fresh Heavy consume the minimal 94,16 g/ plant obtained at combination of plant D1 F2 ( dose urea 50 kg / ha with the moment gift plant and after crop old age two week).